SPORT TURIZMI - Umurzoqov Javohir Fayzullo o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article explores the development, trends and prospects of sports tourism. Research methods include literature analysis, statistical data analysis, and observations. The results show that sports tourism is developing rapidly and contributes to economic growth, as well as the promotion of a healthy lifestyle. It is also emphasized that to further promote sports tourism, it is necessary to strengthen the cooperation of the public and private sectors.